A Survey on MAC Layer Security Challenges in WMNs - K. Ganesh Reddy; P. Santhi Thilagam (New Approaches in Engineering Research Vol. 11, 2021)
For its self-organizing, self-configuring, and self-healing capabilities, as well as their low cost and ease of maintenance, Wireless Mesh Networks (WMNs) have emerged as a potential technology for a wide range of applications. Due to their inherent characteristics such as shared wireless medium, multi-hop and inter-network communication, highly dynamic network topology, and decentralised architecture, securing WMNs is a more challenging and complex issue. The WMNs are vulnerable to a variety of MAC layer attacks because of these vulnerabilities. Existing MAC layer standards and implementations are insufficient to secure these functionalities, and they do not provide comprehensive security solutions to protect both the backbone and the client mesh. As a result, efficient, scalable, and integrated security solutions for WMNs are required. We classify MAC layer attacks and examine existing countermeasures in this paper. Based on the classification of attacks and the analysis of countermeasures, we derive research directions for improving the MAC layer security of WMNs.